PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN AKHLAK SISWA DI SMP NEGERI 2 DIWEK JOMBANG - Fitria Irawarni Mbagho; Ahsanatul Khulailiyah; Desy Naelasari (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
The importance of the teacher's role above and participating in the successful achievement of educational goals, this happens very relevant in moral development is very important for the formation of student attitudes and behavior, in order to become good and moral students because the formation of high morals is the main goal of Islamic education as well as being a guide to live a life according to Islamic teachings. The purpose of this study is to describe the teacher's role in the formation of students' morals at SMP Negeri 2 Diwek. This research is a qualitative field research, the form of the research is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results showed that: the morals of students at SMP Negeri 2 Diwek were good, friendly, and polite. However, there are still those whose morals need to be addressed, such as respecting, obedient, polite, courteous, and shaking hands when they meet. The goal is for students to have an attitude of tolerance for fellow human beings. the application of student morals to teachers is very important, namely respecting teachers, obeying teachers and applying 5S and having character to fellow friends such as helping each other, caring and loving, respecting friends' opinions, and greeting each other at SMP Negeri 2 Diwek, focused on four roles, namely: As educator, mentor, motivator and evaluator in moral formation by holding religious activities, namely dhuhur prayer in congregation, reading the Qur'an, Istiqosah, and commemorating Islamic holidays, as well as the methods used in the formation of students' morals, namely the story method, example, habituation and demonstration.